Norm Detachment: Unwillingness of Millennials to Negotiate - Boylan, Daniel H.; Gallone, Josh; Beerman, Bianca (Journal of Applied Business and Economics, 2021)
Although millennials seem aware of the need for negotiating, salaries paid to starting employees do not always reflect this. It is much more likely for a job candidate to accept an offer for employment without negotiation than it is for a job candidate to bargain for a higher salary. At one point in time bargaining for a higher salary was commonplace. However, due to unknown circumstances millennials seem to be unwilling to negotiate. Our results show that millennials do not negotiate during times viewed as appropriate and times where negotiating could reap substantial benefit. This raises certain questions as to why that may be. We have looked at numerous articles about the behavior of millennials and their skills in negotiating. The results of these articles showed that millennials may not negotiate due to embarrassment or lack of care, but we also found that millennials can be taught how to negotiate. Our research also shows that millennials tend to do things on impulse or for instant gratification.